Calibration principle and structure analysis of the decoupled calibration device for six-axis heavy force sensor. Issue 6 (May 2019) - Lin, Sheng; Sun, Liguang
Abstract: A calibration device of six-axis heavy force sensor based on the parallel orthogonal mechanism is presented. The calibration principle of the force or moment in different direction is proposed. The finite element analysis of the frame and the fixture are conducted. Results show that the deformation influence of the gantry frame and the fixture are small to the calibration error.